Effect of Dynamic Imposition on Mechanical Properties - Ahmad Seng (ICETIA, 2016)
Bendig Rotary is one method appliedto examine material. The aim ofexamination is to reveal the materialability, durability, capability and fatiquedue to dynamic loading. Therefore, wecan identify what parameters affectingmaterial property.Optimal design on a component is veryimportant. This is intended to avoid failure inoperating conditions, because avoidingfailure through excessive designs by using alarge safety factor is a waste. Improperdesign is of course will cause prematurefailure.The research is to apply an experimentalmethod on a laboratory scale where the use ofmetal materials and alloys is certainlyadapted to the condition of the material to beprocessed. The purpose of this research is toknow the effect of loading time on tensilestrength on some material types.